69 Orchestrating joy at work. (3rd November 2019) - Moore, AJS; Stowell, J; Visram, S; Malik, M; Lavelle, M; Wickremasinghe, M
Abstract : Introduction: NHS staff can suffer from burn out, low morale and poor teamwork. Good interdisciplinary teamwork is pivotal to patient centred care. It discourages silo mentality and hierarchical behaviours. Helping staff perform music in an orchestra with their colleagues may augment staff wellbeing, teamwork and inspire joy at work. Methods: Within one year, a Trust Orchestra was created and implemented in a busy London tertiary facility at Imperial College Healthcare Trust, partnering with the associated university. The team was led by a multi-professional group of volunteers, facilitated by the Quality Improvement Team. Ethical approval was not required, as this work was part of a service evaluation. The orchestra involved trust staff or healthcare students who played at the required standard (at least ABRSM Grade 7). This orchestra rehearsed weekly and performed three concerts in the following year. At the end of this intervention period, participants were asked to complete a preliminary survey. They rated how participating in the orchestra had impacted their feelings and work-related behaviours. Creation of the orchestra required significant leadership skills to engage trust staff in the concept and considerable team management skills to facilitate merging of disparate groups. Results: Over 80% of participants attributed the orchestra to a marked increase in happiness, well-being and motivation. 70% reported it helped them relate better to other healthcare professionals and over 60% felt it improved their communication. The orchestra has built a community extending beyond the musicians to the audience, patients, staff and people in the wider local area. Conclusion: Joy at work can be achieved from innovative projects led by passionate individuals. Creative thinking to enable joy at work presents challenging and rewarding opportunities for leadership outside conventional structures within a NHS corporation. Conflicts of interest: Nil to declare.